Turning Followers into Customers: Marketing Communication Strategy of @Aw.Seserahankuningan - Aisyah, Maya Nur; Fahmil Ulum, Tri Nurhamidah; Sriwulandari; Andriany, Dian (Interdiciplinary Journal and Hummanity (INJURITY), 2025)
In the era ever-evolving technology, Instagram has grown into one of the most innovative technology platforms widely used as a promotional medium. Technological advances on Instagram not only facilitate interaction between brands and consumers, but also enable the development more creative and efficient marketing strategies. By effectively utilizing Instagram’s features, Instagram can increase brand awareness, attract new customers, and ultimately increase sales. This study aims to comprehensively analyze the communication strategies employed in the Instagram activities of the @aw.seserahankuningan account and to analyze the factors influenching followers’ trust in becoming customers and their impact on sales growth. The research method used is descriptive qualitative, utilizing the Integrated Marketing Communication (IMC) theory, which is effective for developing promotional programs. Data collection methods include observation, literature review, in-depth interviews with users of the @aw.seserahankuningan Instagram account, and documentation. The results of this study indicate that the @aw.seserahankuningan account has successfully attracted the attention of potential consumers, increased interaction, and build trust. Additionally, Instagram has proven to be an effective tool for promoting products and enchancing wedding gifts branding. The @aw.seserahankuningan account has successfully transformed its followers into loyal customers and supporters who are eager to recommend others to purchase the product.